Pengaruh Anchoring Bias terhadap Kualitas Penilaian Auditor dalam Proses Audit Laporan Keuangan di Perusahaan Go-Public di Indonesia - Judijanto, Loso; Samiun, Aspiati A. (Sanskara Akuntansi dan Keuangan, 2025)
This study investigates the effect of anchoring bias on the quality of auditor judgment in the process of auditing financial statements of publicly listed companies in Indonesia. Anchoring bias, a cognitive bias characterized by undue reliance on prior information, can undermine professional skepticism and judgment accuracy, thereby compromising audit quality. Using a quantitative approach, data was collected from 30 auditors through a structured questionnaire using a 5-point Likert scale. The data were analyzed using SPSS version 26, which showed a significant negative relationship between anchoring bias and audit quality. Regression analysis showed that anchoring bias accounted for 77% of the variance in audit quality (R² = 0.77). The findings highlight the need for interventions such as better training, structured audit procedures, and quality assurance measures to reduce anchoring bias and improve audit quality. This study contributes to the behavioral auditing literature and provides practical insights for audit firms and regulators in Indonesia.